Women Who Emerge as Leaders in Temporarily Assigned Work Groups: Attractive and Socially Competent but Not Babyfaced or Naïve? - Gruber, Freya M.; Veidt, Carina; Ortner, Tuulia M. (Frontiers in Psychology, 2018)
The underrepresentation of women in top positions has been in the spotlight of research for decades. Prejudice toward female leaders, which decreases women’s chances of emerging as leaders, has been discussed as a potential reason. Aiming to investigate the underlying mechanisms of this prejudice, we focused on the question of how facial characteristics (e.g., attractiveness or babyfacedness) might influence women’s leadership emergence. Because other research has related ascribed social competence and ascribed naïveté to attractiveness and babyfacedness, respectively, we hypothesized that ascribed social competence would mediate the impact of ascribed attractiveness on leadership emergence and that ascribed naïveté would mediate the impact of ascribed babyfacedness on leadership emergence. In a pilot study, we analyzed data from 101 participants of a women’s leadership contest held in 2015 in Germany. We then confirmed these results in a methodologically improved main study on other women who participated in the contest in one of two other years: 2016 and 2017 (N = 195). Women applied to participate in the contest by recording their answers to several questions in a video interview. In the contest, they were assigned to teams of about ten women each and worked on several assessment-center-like tasks. After each task, each member of each team nominated the three women they believed showed the best leadership potential in their group. We operationalized women’s leadership emergence as the number of nominations received. We measured participants’ facial attractiveness, babyfacedness, social competence, and naïveté by having raters follow a specifically developed rating manual to rate the answers the women gave in the video interviews. In both studies, the results indicated that women with higher ascribed facial attractiveness had higher ascribed social competence, which significantly predicted leadership emergence in the contest. Likewise, women with higher ascribed babyfacedness had higher ascribed naïveté, which significantly, albeit only slightly, negatively predicted leadership emergence. We discuss the implications of the results for personnel selection.